Evaluation on Symptoms and Self-Treatment due to Radiotherapy and Chemotherapy Based on Different Cancer Stage - Yesiana Dwi Wahyu Werdani; Arief Widya Prasetya (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Cancer modality therapy can minimize metastatic, but it causes decrease in body functions and interfere the daily needs fulfilled. This study was to identify symptoms and self-treatment due to radiotherapy and chemotherapy based on the different cancer stage. This was mixed method design with sequential explanatory approach. Samples were 30 cancer patients taken by purposive sampling at Indonesian Cancer Foundation East Java Branch Surabaya. The instrument was a questionnaire. Fatigue was the most symptoms complained by all patients. Pain, hair loss, constipation were dominated in cancer stage 4, nausea-vomiting, insomnia were dominated in cancer stage 3. The majority self-treatment of fatigue was yoga exercise. Pain and nausea-vomiting were treated by medication and relaxation. Insomnia was treated by mild massage. Constipation was treated by consuming the high fiber foods. Radiotherapy and chemotherapy affect the disturbance of metabolism that cause physical symptoms disorders. Self-treatment by the patient could reduce the symptoms effectively.